Sejarah Kejayaan Dinasti Saljuk, Fatimiyah, dan Mamluk dalam Peradaban Islam - Anisa Dwi Ramadani; Kholid Mawardi (Yayasan Al-Afif, 2026)
This article discusses the important role of three major dynasties, namely the Seljuqs, Fatimids, and Mamluks in maintaining the existence of Islamic civilization during the Middle Ages. This research was conducted because of the decentralization of power after the decline of the central caliphate, which encouraged the emergence of regional powers as guardians of the independence of Islamic regions. The purpose of this research is to analyze several things, namely: (1) how the Seljuq Dynasty contributed to strengthening political stability and educational development, (2) how the Ismaili government model of the Fatimid Dynasty in Egypt worked, (3) the military role of the Mamluk Dynasty in facing attacks from abroad, and (4) how the interaction between these dynasties influenced the occurrence of the Crusades. The method used is library research with a historical and social approach. The research shows that the Seljuq Dynasty strengthened orthodox religion through madrasa institutions, the Fatimids built a new city of civilization in Cairo, while the Mamluks acted as military protectors of Islam against the threat of the Mongols and the Crusaders. The research shows that although each dynasty had a different ideological and ethnic background, the three dynasties together succeeded in maintaining the identity and progress of Islamic civilization amidst the global political crisis that occurred in the Middle Ages.